Haploidentical stem cell transplantation : an emerging treatment modality - Demirer, Taner (Springer International Publishing : Imprint : Humana Press, 2017)
This book discusses the aspects of haploidentical transplants and will shed light on the debates and questions on this burgeoning field and timely topic. Donor selection, graft failure, minimal CD34+ cell requirement, and conditioning regimens used for haploidentical transplants will be written by expert authors dealing with this type of transplants. Approximately one third of the books' chapters cover logic and basic aspects; the remaining two thirds of the book discuss clinical aspects, outcomes, and future perspectives, thus providing a comphrensive discussion of the topic. Haploidentical transplantation is extremely timely, rapidly-changing area and increasing its use will decrease the need for time-consuming, expensive, unrelated donor search. Moreover, Haploidentical Stem Cell Transplantation brings a set of clear answers to questions of feasibility, advantages over unrelated transplants, cost effectivity and outcome.
Keywords: Hematopoietic stem cells -- Transplantation.; Stem cells.; elektronické knihy; electronic books